Clinical Study of Vitamin D3 Deficiency and some Trace Elements in Autism - Husam M. Kredy (Journal of Global Pharma Technology, 2016)
Autism is a disorder of nerve growth characterized by weak social interaction and verbal and nonverbal communication, as well as restricted behavior and stereotypes. The subjects of the study were 90 autistic children with varying degrees of severity (mild, moderate and severe) who were diagnosed with DSM-IV, thirty children in each group and 30 healthy children (age and sex were identical). The boys and girl ratio involved in this study was 4:1, and they were 4-12 years of age. The study showed a significant elevation in the levels of Cu and Pb in the blood sample of autistic children when compared to a healthy control group. The elevation was much pronounced in severe group subjects when compared among autistic groups mild and moderate. The levels of Zn and Vitamin D3 were significantly decreased in autistic children when compared to control. The Zn and Vitamin D3 showed significant variation in blood of severe group children when compared to control group and other study groups. The correlation between Zn and Vitamin D3 in these patient groups were positive. Whereas the correlation between Zn and each of (Cu and Pb) in these patient groups were negative.Keywords: Autism, Children, Blood, Trace Elements, Vitamin D3.